Teachers’ Pedagogical Approaches in Kyrgyzstan: Changes and Challenges - Shamatov, Duishon (Geneva, UNICEF Regional Office for Central and Eastern Europe and the Commonwealth of Independent States., 2012)
This chapter describes pedagogical approaches that are used by teachers in primary and secondary schools of Kyrgyzstan, and presents the results of a study, conducted in 2013, which was designed to increase understanding of pedagogical approaches and thereby contribute to future reforms in national education policies and educational practices for improved learning.
Keywords: teachers’ pedagogical approaches in Kyrgyzstan; changes; challenges